Respon Beberapa Varietas Mentimun (Cucumis sativus L.) Terhadap Pemberian Air Kelapa Tua - Bayu Kusuma; Syakhril syakhril; Bambang Supriyanto (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2012)
Towards of coconut water ripe treatment, and how much ripe coconut water concentration which is good for that, also how both treatment interaction to growth and yield of cucumber. This experiment was conducted from March to May 2012 at the Sempaja street, TVRI building komplex, Samarinda. The experiment was arranged in Completely Randomized Design (CRD) factorial 3 x 6 with 5 replication. The first factor was cucumber varieties (M), i.e. Hercules (m1), Harmony (m2) and Magic (m3). While the second factor was ripe coconut water concentration (K), i.e. 0% (k0l), 10% (k1), 20% (k2) , 30% (k3), 40% (k5), and 50% (k6). Data was analyzed using analysis of variance and continued by Least Significant Different (LSD) of 5%. Results of the experiment showed that : (1) cucumber varieties was hight significantly different on plant height at 10 and 15 days after planting, the number knuckle plant at 20 days after planting, and fruit diameter. Cucumber varieties significantly different on plant height at 20, 25 and 30 days after planting, total fruit per plant, and fresh weight fruit per plant. Cucumber varieties was not significantly different on the knuckle plant at 30 days after planting, the first harvest, the last harvest, and fruit length. The highest of fresh weight fruit at Harmony with 1996,43 grams; (2) the ripe coconut water concentration was very significantly different on plant height at 10, 15, 20 and 25 days after planting, the number knuckle plant at 20 and 25 days after planting. Ripe coconut water concentration was significantly different on the plant height at 30 days planting. Ripe coconut water concentration was not significantly different on the first harvest, the last harvest, total fruit, fruit length, fruit diameter and fresh weight fruit per plant. The highest of fresh weight fruit at concentred 10% with 1945,84 grams: and (3) the interaction between both cucumber varieties and ripe coconut water concentration treatment was not significantly different to all observation variable.